Інтенсифікація екстрагування чорнобривців у роторно-пульсаційному апараті - Белова, Ірина Михайлівна; Гіджеліцький, Віталій Миколайович; Стадник, Ігор Ярославович; Belova, Iryna; Hidzhelitskyi, Vitalii; Stadnyk, Ihor (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті досліджено процес інтенсифікації екстрагування біоактивних сполук із суцвіть чорнобривців (Tagetes patula) у роторно-пульсаційному апараті (РПА) циліндричного типу з гвинтовим ротором. Науково обґрунтовано застосування принципу дискретного введення енергії для підвищення швидкості масообміну. На основі аналізу рівняння руху дисперсної частки визначено роль сил інерції приєднаної маси та гідродинамічного опору в руйнуванні прикордонного дифузійного шару. Установлено, що конструктивні особливості апарата забезпечують високу відносну швидкість фаз, що дає змогу скоротити тривалість екстракції в кілька разів порівняно з традиційними методами, забезпечуючи високий вихід цільових компонентів при оптимальних енерговитратах. /// EN: The article investigates the intensification of bioactive compound extraction from marigold inflorescences (Tagetes patula) using a cylindrical rotary-pulsation apparatus (RPA) with a screw rotor. The application of discrete pulse energy input (DPEI) is scientifically justified to enhance mass transfer rates. Based on the particle motion equation, the role of added mass inertia forces and hydrodynamic resistance in disrupting the boundary diffusion layer is determined. The design features of the RPA ensure high relative phase velocity, significantly reducing extraction time compared to traditional methods while maintaining high yields of target components at optimal energy costs. A fundamental feature of the process in the RPA is the transition from stationary mixing to dynamic impulse action. This relationship is mathematically modeled by integrating the particle motion equation into the mass transfer criteria equation. The study substantiates a shift in the process mechanism: from slow molecular diffusion to forced convection within the micropores of the plant material. The creation of local active zones with high specific power levels enables the minimization of processing time due to the instantaneous destruction of the boundary diffusion layer. Intense particle deformation disrupts intracellular structures and accelerates the release of target components, specifically lutein. Consequently, the process duration is reduced by 5–8 times compared to conventional stationary mixing. The findings demonstrate the high efficiency of the proposed technology for obtaining natural antioxidants for food and pharmaceuticalapplications.
Intensification of marigold extraction via discrete energy input in a rotary-pulsation apparatus
Keywords: чорнобривці; екстрагування; роторно-пульсаційний апарат; дискретне введення енергії; приєднана маса; відносна швидкість; інтенсифікація масообміну; marigolds; extraction; rotary-pulsation apparatus; discrete pulse energy input; added mass; relative velocity; mass transfer intensification; diffusion phase impact